Hapusnya Wewenang Executive Review Pemerintah terhadap Peraturan Daerah: Studi Pasca-adanya Putusan MK Nomor 137/PUU-XIII/2015 dan Nomor 56/PUU XIV/2016 - Lusy Liany (Jurnal ADIL, 2020)
The Constitutional Court, on April 4, 2017, through the Decision No.137/PUU-XIII/2015 has invalidated the enactment of the rules that enabled a Governor to annul Regency/City Laws. On June 14, 2017, with the Decision No.56/PUU-XIV/2016, the Court also invalidated the authority of Ministry of Internal Affair to void Provincial Laws. These decisions brought about a question on whether the government still has the authority to revise those regional laws or it can only be taken through the material review to the judiciary. Based on the background, the authors formulated two problems. Firstly, what is the mechanism of government control of the Regional Regulation after the Constitutional Court Decision Number 137 / PUU-XIII / 2015 and the Court's Decision Number 56/PUU-XIV/2016? Secondly, what are the obstacles to judicial review of regional regulations in the Supreme Court? The research method applied in this paper is a normative method in which qualitative data are gathered and the statute and conceptual approaches are employed. First result, the government, both the Minister of Internal Affairs and the Governor, can oversee the regional law-making process through the executive preview mechanism and the annulation of both Province and Regency/City Laws is in the domain of the Supreme Court's authority. Second, the judicial review process in the Supreme Court has not fully met the legal principles of judicial review process, as it is not open to public, there is no deadline to finish the trial, and the Supreme Court’s decision is not supported by sufficient details of judges’ legal opinion.